Variability in reproductive traits in the sex-changing fish, Coris julis, in the Mediterranean - ALONSO-FERNANDEZ, A.; ALOS, J.; PALMER, M. (Mediterranean Marine Science, 2013)
The quantity and quality of propagules, i.e., reproductive output, play a key role in the dynamics of exploited populations, with particular implications for sex-changing fish. Here, we studied for the first time the effects of maternal traits on the reproductive output of the Mediterranean rainbow wrasse Coris julis, a sequential hermaphroditic fish widely distributed in temperate marine coastal regions. The quantity of the reproductive output (batch fecundity) was significantly related to maternal size, which is of special interest in a species submitted to size-selective harvesting (recreational angling). However, egg quality (egg size) was not significantly related to any maternal factor and the spawning fraction was related to a seasonal pattern only. These results should contribute to improving estimations of the annual reproductive output and the stock assessment of this species and some implications for management are discussed.